Perancangan Kawasan Wisata Danau Masjid Koto Kari Dengan Pendekatan Arsitektur Kontekstual - Saputra, Didi; Husaini, Muhd Arief Al; Hidayat, Wahyu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The Koto Kari Mosque Lake Tourism Area is one of the natural features in Kuantan Singingi Regency that has the potential to become a major tourist attraction. Many tourists flock to the area because of its alluring possibilities. The provision of suitable facilities to enable tourism activities does not support the existing potential. As a result, it is vital to set up a good area by paying attention to the potential that exists in the region so that it may be utilized optimally while maintaining the area's qualities. The goal of this research is to come up with a plan for an area that can comfortably accommodate tourist activities. The topic of Contextual Architecture is applied to the design concept of the Koto Kari Mosque Lake tourist area. The research technique is a qualitative method that uses a logical approach to conduct descriptive research. Data was gathered through field investigations, interviews, and documentation. The findings of this study show that using a contextual architectural strategy to create the Koto Kari Mosque Lake tourist area is the best option. The region's design with this theme is intended to be able to create a tourism area arrangement that blends in with the local area's still-standing buildings. So that guests who come not only to travel but also to experience the distinctive ambiance of the tourist region can do so with the help of contextual architecture.Keywords : Tourist Areas, Lakes, Contextual Architecture